The structure of the proteins of Camp Hill virus - Sunil Thomas (PLoS ONE, 2025)
Camp Hill virus (CHV), a newly identified henipavirus, was recently discovered in northern short-tailed shrews in Camp Hill, Alabama. This marks a significant event as it is the first henipavirus ever reported in North America. The significance of henipaviruses lies in their ability to cause severe and often fatal diseases, such as encephalitis and respiratory illness, with a high mortality rate in both humans and animals. The emergence of new henipavirus strains, like CHV, amplifies concerns about the possibility of future zoonotic spillovers—where diseases are transmitted from animals to humans. Because henipaviruses can be highly contagious and have no specific antiviral treatment, their emergence poses a potential threat to public health. The major proteins of CHV include attachment glycoprotein, fusion protein, X protein, C protein, matrix protein, nucleocapsid protein, phosphoprotein, and RNA polymerase. In our study, we focused on determining the three-dimensional structure of these major proteins, providing crucial insights into how they function at the molecular level. Understanding the precise structure of these proteins is vital, as it can inform efforts to block the virus’s ability to infect cells. Proteomic analysis confirmed that the proteins of CHV is similar to the proteins of Sollieres shrew parahenipa virus, Ninorex virus, Melian virus, Lechodon virus and Langya virus. We identified the B-cell and T-cell epitopes of these proteins. By characterizing these epitopes, our research contributes to the design of targeted vaccines that could stimulate a robust immune response against CHV. The identification of these epitopes also allows us to understand how the virus interacts with the immune system, which is essential for designing vaccines that can elicit both humoral and cellular immunity. Our study would lead to development of novel vaccines to protect against CHV.